2019
DOI: 10.1177/0024363919884799
|View full text |Cite
|
Sign up to set email alerts
|

Is Research on Transgender Children What It Seems? Comments on Recent Research on Transgender Children with High Levels of Parental Support

Abstract: Recent research on transgender children who have had support from their parents for their transitioning has concluded that their mental health is virtually no different than that of nontransgender children. Such research has been extensively cited, over 370 times in the past three years. Most of the hundreds of reviews received the stated results of the studies with little caution. However, the research featured numerous statistical errors and omissions, the implications of which would likely lead neutral obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 53 publications
(111 reference statements)
0
9
0
Order By: Relevance
“…One way that this occurs may be through a tendency for scholars to cite research findings favorable to their causes while ignoring/not citing contradictory evidence. It has been found that authors were far more likely to cite research that was favorable for same-sex families, even their own research (Schumm 2010a; Schumm and Crawford 2020a) than to cite research that was not favorable. As an example, Goldberg, Bos, and Gartrell (2011) found that nearly 60% of the offspring of lesbian mothers, by age 17, had used illegal drugs, compared to about a fifth of the children of heterosexual parents, a substantial and statistically significant difference.…”
Section: Confirmation Bias In Social Sciencementioning
confidence: 99%
See 1 more Smart Citation
“…One way that this occurs may be through a tendency for scholars to cite research findings favorable to their causes while ignoring/not citing contradictory evidence. It has been found that authors were far more likely to cite research that was favorable for same-sex families, even their own research (Schumm 2010a; Schumm and Crawford 2020a) than to cite research that was not favorable. As an example, Goldberg, Bos, and Gartrell (2011) found that nearly 60% of the offspring of lesbian mothers, by age 17, had used illegal drugs, compared to about a fifth of the children of heterosexual parents, a substantial and statistically significant difference.…”
Section: Confirmation Bias In Social Sciencementioning
confidence: 99%
“…However, a review of her raw data undermines that claim” (p. 8). Vadevelu and Arunberkfa (2022) cited Schumm and Crawford (2020) in connection with their convenience sampling plan (p. 6) and with respect to future research (p. 12), along with many other articles that they cited. Thus, three of the four citations ignored the essential findings of Schumm and Crawford (2020b), which may either reflect confirmation bias or the difficulty in overturning incorrect but widely cited results.…”
Section: Confirmation Bias In Social Sciencementioning
confidence: 99%
“…For example, Olson (2016) argued that transitioning children with parental support have the same levels of psychopathology as controls. However, a review of her raw data undermines that claim (Schumm and Crawford, 2020).…”
Section: The Current Controversy Describedmentioning
confidence: 99%
“…Even though there has been some debate in the literature as to the relative protective benefits associated with parental support for youth with gender dysphoria (Schumm and Crawford, 2020 ), the larger literature consistently underscores the importance of parental support and secure attachment in promoting adolescent well-being. There are likely diverse trajectories among youth with gender dysphoria as they strive toward self-understanding, self-expression, and developing connections in the community.…”
Section: Introductionmentioning
confidence: 99%